Reactivity of Routine HIV Antibody Tests in Children With Perinatally Acquired HIV-1 in England: Cross-sectional Analysis. Issue 2 (February 2019) - Fidler, Katy J.; Foster, Caroline; Lim, Emma J.; Patel, Amie; Welch, Steven; Menson, Esse; Klein, Nigel; Judd, Ali
Abstract : We assessed HIV antibody prevalence in children with perinatally acquired HIV in England. Eighteen percent (10/55) of those starting combination antiretroviral therapy <6 months of age were seronegative at median age 9.1 years and had lower viral load at diagnosis and combination antiretroviral therapy start and fewer viral rebounds, than 45 of 55 seropositives. Implications for patient selection for HIV cure research, and interpretation of routine antibody testing, are discussed.